Intractable pruritus during outpatient epidural hydromorphone infusion: A case report and a focused review of the literature - Ruan, MD, Xiulu; Ma, MD, PhD, Li; Couch, MD, J. Patrick; Chen, MD, PhD, Tao; Bumgarner, PhD, Gary W. (Journal of Opioid Management, 2015)
Background: Intraspinal drug delivery therapy has been increasingly used in patients with intractable, nonmalignant pain who have failed to respond to conventional treatment or cannot tolerate systemic opioid(s) due to adverse events. By infusing a small dose of an opioid analgesic directly into the cerebrospinal fluid, near opioid receptors, profound spinal analgesia can be obtained. Before the implantation of permanent intraspinal pump, a neuraxial opioid infusion trial is usually conducted to demonstrate the effectiveness of neuraxial opioid for analgesia. Patient-controlled epidural opioid infusion trial, performed in an outpatient setting, is one of the approaches used to conduct such a trial. Objective: To report a case of severe pruritus observed during the continuous epidural hydromorphone infusion trial and to conduct a focused review of the literature. Case report: An otherwise healthy 56-year-old lady, with a 4-year history of severe low back pain and bilateral leg pain due to failed back surgery syndrome, was referred to our clinic for intraspinal drug delivery therapy. Following a preimplantation psychological evaluation confirming her candidacy, she consented to an outpatient patient-controlled continuous epidural hydromorphone trial. A tunneled lumbar epidural catheter was placed at L3-L4 with catheter tip advanced to L2 under fluoroscopic guidance. Satisfactory catheter placement was confirmed by epidurogram. The catheter was then tunneled subcutaneously and connected to a Microject™ patient-controlled epidural analgesia (PCEA) pump (Codman, Raynham, MA). The pump was programmed to deliver hydromorphone 0.3 mL/h (0.06 mg, concentration 0.2 mg/mL) at basal rate of 0.3 mL/h, with bolus dose set at 0.2 mL (0.04 mg) and 30-minute lockout interval. The patient was instructed how to operate the infusion pump prior to discharging home. During the infusion trial, she reported satisfactory analgesia (>90 percent pain reduction) and was able to reduce her oral opioid dose by more than 80 percent. However, she developed severe, persistent itching, unresponsive to meticulous epidural infusion titration or various antipruritic treatments. Her pruritus remained severe and unabated until a few hours after the termination of the epidural hydromorphone infusion. Conclusion: Pruritus may occur and persist during epidural hydromorphone infusion. This report describes severe pruritus in a patient on epidural hydromorphone administration, in the setting of an outpatient infusion trial.